Living ice cream / Muhammad Aliff Fauzan Fazli, Muhammad Aidil Iskandar A Malik & Muhamad Firdaus Azhari - Fazli, Muhammad Aliff Fauzan; A Malik, Muhammad Aidil Iskandar; Azhari, Muhamad Firdaus (2023)
We decided to sell ice cream as our line of work, and it comes in a variety of flavours like Toasted Hazelnut with Chocolate, Blackberry frozen yoghurt, and Watermelon Sorbet. This allows us to consistently deliver high customer satisfaction by offering flavours that are dependable, enjoyable, and affordable. The target market for this ice cream is young and old people who want dessert in the vicinity of Johor Bahru, Johor. A competitive advantage sets a business apart from its rivals. We need to do much more than just sell ice cream to clients in order for this firm to be successful. This company provides extra services like delivery and a free sample for new customers so they will be confident enough in our company after purchasing and tasting our ice cream to return and place another order